Edukacja zdrowotna i seksualna na łamach „Świata Płciowego” (1905-1906) - Bednarz-Grzybek , Renata; Krasińska, Izabela (Studia Edukacyjne, 2020)
Health education is related to the health promotion. This is a process aimed to shaping people’s habits of taking care of their and other people’s health. The sexual education can be considered as one of the health education departments. The article attempts to show the answer to the question how in the pages of the “Sexual World” coming out in Lviv in 1905-1906, how to prevent and cope during the illness was taught, and suggested where to look for the medical care, especially in the case of venereal diseases, which are often side effects of prostitution.